Extraction, Purification and Pharmacological Activity of Melon Pedicle Active Ingredients - Geng, Xu; Li, Kun; Wang, Fei; Pan, Taowen; Diao, Yunpeng; Lin, Yuan (Asian Journal of Chemistry, 2014)
The present study was designed to characterize the effects of the extraction of melon pedicle on the contractility of isolated jejunal smooth muscle segment and its underlying mechanism. The investigation of single factor and orthogonal test was adopted to optimize the extraction and purification of melon pedicle, using the content of total saponins in entirfel preparation as the evaluation indicator; ex vivo assay was selected as the major method to determine the effects of the extraction separated from melon pedicle on the contractility of isolated jejunal smooth muscle segment (IJSMS). The optimum extraction conditions was to extract at 50 °C, with water as the solvent, the drug-water ratio of 1:60, extracted for 1.5 h, three times with the total saponins content of 1.8447 %; The optimal condition for purification of total saponins using 10 g HP-20 resin as follows. The resin column diameter-height ratio of 17:305, eluted with 12BV of 30 % ethanol and the elution flow rate of 1 mL/min are the optimal elution conditions, with the total saponins content of 8.3031 %. The stimulation of IJSMFS with M receptor and H1 receptor independent. No further stimulation effects of EFMP were observed in the presence of verapamil or in Ca2+-free condition, indicating EFMP-induced stimulation effects are Ca2+-dependent and the action of EFMP on intestinal motility was mediated by Ca2+ influx through L-type Ca2+ channel.